In Vitro Propagation of Chinese Potato (Plectranthus rotundifolius (Poir.) J.K. Morton) Through Axillary Shoot Bud Culture - Indira, Asha; NK, Dwivedi; A., Indira Devi; R, Asokan Nair (JOURNAL OF ROOT CROPS, 2015)
An efficient and cost effective in vitro plant regeneration protocol through single nodal segment culture was achieved in the minor tropical tuber crop, Chinese potato (Plectranthus rotundifolius (Poir) J.K. Morton), through axillary shoot bud proliferation in Murashige and Skooge medium augmented with varying concentrations of 6-benzylaminopurine (BAP) and Kinetin (0.5.2.0 mg l-1). BAP at 1 mg l-1 was the most effective medium for multiple shoot induction, which gave an average of 38 shoots/ node, followed by Kinetin (0.5 mg l-1) inducing 22 shoots/node as compared to the other concentrations of hormones and MS basal medium alone, after 45 days of culture. MS basal medium, though not promoting shoot multiplication, gave higher shoot length with elongated internodes. In vitro multiplied shoots transferred to MS medium with 0.5 mg l-1 IBA was optimum for healthy rooting. Rooting of the micro shoots also occurred in the Kinetin containing shoot multiplication medium itself from the base and nodes on ageing of the cultures after 85 days of culture. The healthy and vigorous in vitro regenerated micro shoots were separated out and were hardened upon transfer to plastic cups with sterile soil and sand. These were successfully acclimatized ex vitro in pots with potting mixture under green house conditions for four weeks. The survival rate was 90% and the plants that established in the green house resembled the mother plants in habitat without any morphological variations. This very simple and efficient protocol can be used to mass propagate elite stable clones of this very important aromatic tropical minor tuberous vegetable.